2014
DOI: 10.1155/2014/838101
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents and Toxicity of Duguetia furfuracea Hydroalcoholic Extract in Drosophila melanogaster

Abstract: Duguetia furfuracea is frequently used as a medicinal plant in Brazil. However, studies have evidenced its cytotoxic, bactericide, and antitumor activities. In the present study we aimed to evaluate the potential toxicity of hydroalcoholic leaves extracts of D. furfuracea (HEDF) in a Drosophila melanogaster model. Toxicity was assessed as changes in locomotor performance, mitochondrial activity, oxidative stress, MAPKs phosphorylation, and apoptosis induction after exposure to HEDF concentrations (1–50 mg/mL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The chromatographic profile of HEDF demonstrated the presence of caffeic acid and rutin as major compounds (33.17 ± 0.03 mg/g and 20.05 ± 0.01 mg/g, resp.) while gallic acid (5.29 ± 0.01 mg/g) and catechin (5.31 ± 0.01 mg/g) were the least abundant [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chromatographic profile of HEDF demonstrated the presence of caffeic acid and rutin as major compounds (33.17 ± 0.03 mg/g and 20.05 ± 0.01 mg/g, resp.) while gallic acid (5.29 ± 0.01 mg/g) and catechin (5.31 ± 0.01 mg/g) were the least abundant [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mt-OH and Ac-OEt fractions were submitted to the chromatographic analysis of reversal phase. The chemical composition of the HEDF was previously determined by our group [ 6 ] using the same procedure described in this section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic effects of Duguetia plants have been evaluated in different models (Coelho et al, 2011;Sousa et al, 2012;Silva et al, 2012;Silva et al, 2013;Rodrigues et al, 2015;Pinho et al, 2014). Silva et al (2012) have demonstrated via the lysogenic induction test (SOS-Inductest) and mouse bone marrow micronucleous assay that Duguetia furfuracea lyophilized leaf extract has cytotoxic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2012) have demonstrated via the lysogenic induction test (SOS-Inductest) and mouse bone marrow micronucleous assay that Duguetia furfuracea lyophilized leaf extract has cytotoxic activity. The hydroalcoholic extract of D. furf uracea leaves has been s hown to cause t oxicity in Dros ophila melanogaster aft er 7 days of exposure, with a reduction of viability that was associated with increasing of oxidative stress and a reduction of antioxidant enzymes in flies (Pinho et al, 2014).…”
Section: Resultsmentioning
confidence: 99%